Can Hybrid Arterial Spin Labeling‐Tagged Zero‐Echo‐Time Magnetic Resonance Angiography Be an Effective Candidate in the Evaluation of Intracranial Artery Diseases? A Clinical Feasibility Study. Issue 3 (20th May 2021) - Shang, Song'an; Wang, Lijuan; Ye, Jing; Luo, Xianfu; Zhang, Hongying; Dou, Weiqiang; Wu, Jingtao; Li, Daixin
Abstract : Background: Flow related artifacts in continuous arterial spin labeling (cASL) zero‐echo‐time (ZTE) magnetic resonance angiography (MRA) could influence the vasculature visualization. Purpose: To investigate the clinical feasibility for the intracranial artery diseases assessment by utilizing hybrid ASL‐ZTE‐MRA (hASL‐ZTE‐MRA). Study Type: Prospective, technical development. Population: Sixty‐seven subjects with known/suspected cerebrovascular diseases. Field Strength/Sequence: Gradient echo based cASL‐/hASL‐ ZTE‐MRA at 3.0 T. Assessment: Subjective/objective evaluation for sound‐levels. Image quality (IQ), signal‐to‐noise ratio (SNR), and contrast‐to‐noise ratio (CNR) were analyzed within artery segments. Stenotic grading, aneurysm measurement, and signal intensity of lesions were further analyzed. Statistical Tests: Kolmogorov–Smirnov test for data normality check. Between two MRAs: Wilcoxon signed‐rank test for sound experience/IQ ratings analysis; Paired t test for SNR/CNR comparison. One‐way analysis of variance for sound intensity comparison. For stenosis grading/aneurysm measurement: Kendall's W test/intraclass correlation coefficient (ICC) for interobserver agreement test within each modality, weighted kappa statistics/ICC for intermodality agreement test between each MRA and computed tomography angiography. Results: Sound‐level perception/intensity was similar ( P = 0.86, P = 0.55) between MRAs. The mean IQ score for hASL‐ZTE‐MRA was on diagnostic scale and slightly higher ( P < 0.05) than that of cASL‐ZTE‐MRA. hASL‐ZTE‐MRA provided higher ( P < 0.05) SNR/CNR than that of cASL‐ZTE‐MRA. Signal uniformity was improved on hASL‐ZTE‐MRA, particularly among the anterior circulation ( P < 0.05). Comparing to cASL‐ZTE‐MRA, on hASL‐ZTE‐MRA, stenotic lesions were accurately assessed; flow in the stent or aneurysm remnant was better depicted ( P < 0.05); AVM nidus was preferred with increased SNR ( P < 0.05). No significant differences for the aneurysm measurement were found between MRAs ( P = 0.95), in addition to the slightly higher SNR ( P < 0.05) on hASL‐ZTE‐MRA. Data Conclusion: Comparing to cASL‐ZTE‐MRA, hASL‐ZTE‐MRA is robust and feasible for the evaluation of intracranial artery diseases with diagnostic IQ, improved vessel contrast, and better signal heterogeneity. Level of Evidence: 2 Technical Efficacy: 2